Poverty: A Socio-economic Disease and Causative Agent of Numerous Socio-economic Diseases - Babalola, Sikiru Jimoh; Mohd, Saidatulakmal (School of Social Sciences, USM, 2017)
The overall objective of this paper is to point out that poverty is a disease as well as a host to many social economic diseases. A navigation through the literature reveals that despite reported mixed findings of the effect of poverty on some socio-economic problems, it is still one of the leading causes of such problems. Thus, the need to channel a lot of resources and efforts towards combating it becomes compelling for two broad reasons. First, tackling poverty properly will indirectly reduce many vices confronting both developing and developed countries. Such problems include, but not limited to terrorism, robbery, corruption, social unrest, among others.Second, it is economically rational to commit adequate resources to tackle poverty now with a view to indirectly conserving resources for future development projects.